59.7k views
4 votes
8 thank you so much!!!

8 thank you so much!!!-example-1

2 Answers

6 votes

Answer:

(-4,2)

Explanation:

answers are shown and pictured

8 thank you so much!!!-example-1
User Holly
by
4.5k points
3 votes

Answer:

C) (-4, 2)

Explanation:

It is easier to begin by putting the y equation back into the x equation so it would be rewritten as:

x= 2 (-2x - 6) - 8

Since you replace the y for the given y value

Distribute and you get

x = -4x -12 -8

Add 4x to both sides to get rid of it on the right and balance the equation

5x = -12-8 which is -20

5x = -20

divide by 5 gives you the value -4 for the x

Now simply put that value in for the y equation

y= (-2 (-4)) -6

y = 8 - 6

y = 2

User Remco Ros
by
4.4k points